Action research on a collegial model of peer observations. Issue 4 (8th August 2018) - Tezcan-Unal, Burcu
Abstract: Observing peers for professional development is a familiar and valuable practice but not always favoured in many educational institutions. This small-scale action research (AR) was conducted in an institution where teachers are accustomed to regular peer observation, requiring each teacher to conduct peer observation and to reflect in their teachers' portfolios. Conventionally, to fulfil the requirement each teacher finds a colleague to observe them either with or mostly without a certain focus. This study, however, employed action research methodology to inquire into a collegial peer observation model to improve this organisational practice. It aimed to promote mutual growth of the participating faculty members in an agreed area. Including the author, five faculty members, who are midcareer and experienced English language teachers, acted as members of the consultation group . In the AR project, appreciative inquiry was used when reflecting on the observed classes and during focus group interviews. As a result of this AR, at least two levels of knowledge were generated: first-person (author) and second-person (the team). The knowledge claim that this practitioner research constructed is 'When small groups of teachers conduct peer observations focusing on a common concern, learning and collegial growth may increase.' It is expected to lead to a third-person stage in the department and the academic community in general.